Cardiac rhabdomyosarcoma - Damjanović Miodrag R.; Tomašević Miloje; Đordević-Radojković Danijela; Koraćević Goran; Janković Ružica (Vojnosanitetski Pregled)
Background. Primary malignant cardiac tumors are rare entities and rhabdomyosarcoma accounts 20% of these lesions. Case report. We presented a female patient with loss of appetite and loss of weight. She also had symptoms of heart failure and bilateral pleural effusions. A mobile tumor in the left heart with the entrance from the left atrium to left ventricle during diastole was seen by transthoracic echocardiography. The tumor was extirpated in total, histologic diagnosis was rhabdomyosarcoma, and the patient died after 6 months. Conclusion. Primary malignant cardiac tumors can simulate heart failure or systemic disorders. Cardiac rhabdomyosarcomas have a poor prognosis with the average survival of 6 months after the occurrence of symptoms and making a diagnosis. In cardiac insufficiency, differential diagnostics should be used to consider cardiac tumors that could be with certainty confirmed or excluded by echocardiography.